2020
DOI: 10.1002/ajh.25778
|View full text |Cite
|
Sign up to set email alerts
|

Statin use is associated with improved survival in multiple myeloma: A Swedish population‐based study of 4315 patients

Abstract: Statin use has been associated with reduced cancer‐specific mortality among patients with several cancer types, including multiple myeloma (MM). We aimed to further elucidate the association of statin use and dose intensity with MM survival. Using Swedish population‐based national health registers, we identified all incident MM diagnoses occurring January 1, 2007 to December 31, 2013 and their drug dispensations and comorbidities. We assessed statin exposure in 6‐month periods pre‐ and post‐diagnosis, treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…We, and others, have demonstrated that statins induce apoptosis in a subset of MM cell lines by directly inhibiting HMGCR, indicating that some MM cells are dependent on the MVA pathway for survival [8][9][10][11]. These preclinical data are supported by recent retrospective analyses, where statin use was associated with reduced MMspecific mortality [12,13]. Moreover, phase I/II trials in patients with relapsed/refractory MM have reported promising responses when a statin was combined with standard-of-care therapies in some, but not all, patients [14,15].…”
Section: Introductionsupporting
confidence: 68%
“…We, and others, have demonstrated that statins induce apoptosis in a subset of MM cell lines by directly inhibiting HMGCR, indicating that some MM cells are dependent on the MVA pathway for survival [8][9][10][11]. These preclinical data are supported by recent retrospective analyses, where statin use was associated with reduced MMspecific mortality [12,13]. Moreover, phase I/II trials in patients with relapsed/refractory MM have reported promising responses when a statin was combined with standard-of-care therapies in some, but not all, patients [14,15].…”
Section: Introductionsupporting
confidence: 68%
“…Some inconsistent results were reported. Retrospective studies showed that statin treatment prolonged the survival of patients with multiple myeloma, colorectal cancer, and metastatic pancreatic cancer cotreated with first-line chemotherapy ( Abdel-Rahman, 2019 ; Brånvall et al, 2020 ; Cardwell et al, 2014 ). In contrast, randomized phase III trials in patients with SCLC, metastatic colorectal cancer, HCC, or gastric cancer showed that addition of pravastatin or simvastatin to standard chemotherapy offers no additional benefit ( Jouve et al, 2019 ; Kim et al, 2014 ; Lim et al, 2015 ; Seckl et al, 2017 ).…”
Section: Targeting Lipid Metabolism For Cancer Treatmentmentioning
confidence: 99%
“…Farooqui reviewed different randomized controlled trials and concluded that the addition of statins to standard chemotherapy is not able to enhance the survival in patients with advanced cancers and a prognosis of less than 2 years ( 195 ). A Swedish study, instead, concluded that statins use for 6 months in patients with multiple myeloma enhanced the survival rate of both men and women ( 196 ). In another study, atorvastatin was administered in patients with prostate cancer for 27 days before prostatectomy.…”
Section: Cholesterol Metabolic Reprogramming In Cancer: Pharmacological Targetingmentioning
confidence: 99%